2016
DOI: 10.1016/j.econlet.2016.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant volunteering: A way out of labour market discrimination?

Abstract: Many governments encourage migrants to participate in volunteer activities as a stepping stone to labour market integration. In the present study, we investigate whether this prosocial engagement lowers the hiring discrimination against them. To this end, we use unique data from a field experiment in which fictitious job applications are sent in response to real vacancies in Belgium. Ethnic origin and volunteer activities are randomly assigned to these applications. While non-volunteering native candidates rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 15 publications
3
38
0
Order By: Relevance
“…8 Both callback rates are comparable to those measured in former correspondence experiments. In particular, these numbers corroborate with those of the recent Flemish correspondence experiment discussed in Baert and Vujić (2016). The Flemish (Turkish) candidate in their experiment got an invitation in 9.7% (6.4%) of his applications.…”
Section: Table 1 About Heresupporting
confidence: 77%
See 1 more Smart Citation
“…8 Both callback rates are comparable to those measured in former correspondence experiments. In particular, these numbers corroborate with those of the recent Flemish correspondence experiment discussed in Baert and Vujić (2016). The Flemish (Turkish) candidate in their experiment got an invitation in 9.7% (6.4%) of his applications.…”
Section: Table 1 About Heresupporting
confidence: 77%
“…Employing extensive field experiments, during the past decade, scholars have shown that discrimination is still a barrier for ethnic minorities in the labour market (Baert et al, 2015;Baert & Vujić, 2016;Booth et al, 2012;Carlsson & Rooth, 2007;Kaas & Manger, 2012;Neumark, In press). Identifying ethnic discrimination is, however, one thing; tackling it is another.…”
Section: Introductionmentioning
confidence: 99%
“…Second, future studies should evaluate how criminal background interacts with other individual traits, especially those that are known to have a negative impact on people's employability. We know, for example, that immigrants are discriminated against in the labor market in most European countries (see, e.g., Baert et al 2017;Baert and Vujić 2016;Carlsson and Rooth 2007;Midtbøen 2016). Do immigrants with a criminal background then face a double penalty in the hiring situation?…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 34 empirical studies document negative effects, while two studies find no differences between minorities and majorities, and one study reports an-in that particular context-expected positive effect of being from the minority group (Baert 2017, 6). In the specific Flemish context in which we are interested, four studies unanimously document negative effects of minority group names on callbacks (Baert and Vujic 2016;Baert et al 2015Baert et al , 2017Capeau et al 2012). In comparison, evidence of gender discrimination is mixed and heterogeneous across different occupations, with effects indicating both discrimination of men and women as well as no discrimination at all (Baert 2017).…”
Section: Discrimination In Hiring Decisionsmentioning
confidence: 99%